2022
DOI: 10.2196/39531
|View full text |Cite
|
Sign up to set email alerts
|

Pain Reduction With an Immersive Digital Therapeutic Tool in Women Living With Endometriosis-Related Pelvic Pain: Randomized Controlled Trial

Abstract: Background Chronic pelvic pain is a common and disabling condition in women living with endometriosis. Pharmacological and surgical treatments are not always effective at controlling pain and present important restrictions. Digital therapeutics (DTx) are emerging as major nonpharmacological alternatives that aim to extend the analgesic therapeutic arsenal of patients. Objective In this randomized controlled trial (RCT), we aimed to measure the immediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
16
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 54 publications
6
16
1
1
Order By: Relevance
“…This study also confirmed the effect of VR itself (digital control) when associated with nature sounds, which is already used to reduce pain during surgery or for patients in intensive care [39,40]: its immersive effect has a direct impact on pain as observed in previous work [22,28,29,[41][42][43][44][45][46][47][48][49][50][51]. Interestingly, compared to our previous study [24], the upgraded sham delivering the same audio/video content but in an immersive VR headset instead of a tablet achieved higher pain intensity reduction when used on a similar population.…”
Section: Pain Intensity and Pain Reliefsupporting
confidence: 89%
See 1 more Smart Citation
“…This study also confirmed the effect of VR itself (digital control) when associated with nature sounds, which is already used to reduce pain during surgery or for patients in intensive care [39,40]: its immersive effect has a direct impact on pain as observed in previous work [22,28,29,[41][42][43][44][45][46][47][48][49][50][51]. Interestingly, compared to our previous study [24], the upgraded sham delivering the same audio/video content but in an immersive VR headset instead of a tablet achieved higher pain intensity reduction when used on a similar population.…”
Section: Pain Intensity and Pain Reliefsupporting
confidence: 89%
“…However, most studies on VR for pain have been conducted in a medical context under the supervision of a health care team [24][25][26][27] and only few are conducted at patients' homes with treatment self-administered by the patients themselves [28]. In fact, most of the medical devices developed to treat pain, either acute or chronic, are designed to be used by medical staff in a medical setting [24,27,[29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…However, despite these issues, our sensitivity analysis still showed a significant effect across all clinically important outcomes in all retrieved studies; it is unlikely that this is due to chance alone. Furthermore, the analgesic effect of VR is not limited to CNNP, studies in chronic low back pain, 43 traumatic and nontraumatic pain in emergency patients, 44 and endometriosis-related pelvic pain 45 show significant pain modulation effects of VR. These reports suggest that the use of VR may be effective for other types of acute and chronic pain.…”
Section: Discussionmentioning
confidence: 99%
“…There is also increasing interest both from researchers and general public in ‘femtech’ broadly and how it can be applied to endometriosis. However, it is important for such advances to be tested thoroughly, with rigorous clinical trials with appropriate placebo controls [46 ▪ ]. When new technologies are developed and marketed without full clinical trials, a rift is created between consumer healthcare markets and clinical guidelines [43,47].…”
Section: Future Workmentioning
confidence: 99%